CHROMOLAENA ODORATA: AS NATURE’S WOUND HEALER - BHUYAN, MONMOYURI; DEB, PULAK; DASGUPTA, DEBAPROTIM (International Journal of Current Pharmaceutical Research, 2019)
According to the world health organization, more than 80% of the world’s population relies on traditional medicine for their primary health needs. The use of herbal medicines represents a long history of human interactions with the environment. The study of wound-healing plants has acquired an interdisciplinary nature with a systematic investigational approach. Several biochemical are involved in the healing process of the body, including antioxidants and cytokines. Phytochemicals or biomarkers from numerous plants suggest they have positive effects on different stages of the wound healing process via the various mechanism. Injury to the soft tissues is followed by wound healing, which consists of four stages: hemostasis, inflammation, proliferation and remodeling. Chromolaena odorata is a weed that is traditionally used for the treatment of various ailments in humans and animals. However, it exhibits anti-inflammatory, antipyretic, analgesic, antimicrobial, cytotoxic and numerous other relevant medicinal properties on an appreciable scale, and is known in some parts of the world as a traditional medicine used to treat various ailments. To understand its specific role as nature's gift for healing wounds and its contribution to affordable health care, this plant must be scientifically assessed based on the available literature. This review aims to summarize the role of C. odorata and its biomarkers in the wound healing activities of biological systems, which are crucial to its potential future use for the treatment of wounds.